2012
DOI: 10.1111/j.1365-3156.2012.02981.x
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐up of TB and HIV programme collaborative activities in Zambia – a 10‐year review

Abstract: Abstractobjective To review the activities, progress, achievements and challenges of the Zambia Ministry of Health tuberculosis (TB) ⁄ HIV collaborative activities over the past decade.methods Analysis of Zambia Ministry of Health National TB and HIV programme documents and external independent programme review reports pertaining to [2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010]. conclusions The scale-up of TB ⁄ HIV collaborative programme activities in Zambia has steadily increased over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 5 publications
2
30
2
1
Order By: Relevance
“…This was higher than CPT uptake reported in another study carried out in Addis Ababa which reported that only 43.6% patients benefited from CPT (Denegetu and Dolamo, 2014) while in a referral hospital in North-West Ethiopia, 45.9% of patients eligible for CPT actually received treatment (Alemayehu (Kapata et al, 2012). The possible reasons for a relatively higher CPT uptake in the present study might be attributed to trainings provided to health workers on importance of initiation of CPT.…”
Section: Discussioncontrasting
confidence: 55%
“…This was higher than CPT uptake reported in another study carried out in Addis Ababa which reported that only 43.6% patients benefited from CPT (Denegetu and Dolamo, 2014) while in a referral hospital in North-West Ethiopia, 45.9% of patients eligible for CPT actually received treatment (Alemayehu (Kapata et al, 2012). The possible reasons for a relatively higher CPT uptake in the present study might be attributed to trainings provided to health workers on importance of initiation of CPT.…”
Section: Discussioncontrasting
confidence: 55%
“…The prevalence of HIV among the TB cases tested in the survey was up to five times lower than routinely reported among clinical cases at facility level in the programmatic setting, where co-infection rates of 60–62% are reported [9, 15]. This implies that facility based data on co-infection rates alone may not reflect the true epidemiological picture of the general population.…”
Section: Discussionmentioning
confidence: 80%
“…The difference is likely explained by two processes. On the one hand, TB-HIV co-infected patients are known to have poorer treatment outcomes [9] and therefore TB/HIV co-infected patients who do not seek care or cannot access care are likely to die early and do not remain as prevalent cases in the community. Furthermore, it is possible that TB/HIV co-infected individuals who fall sick are more likely to go to the health facility earlier because of the severity of symptoms and are thus potentially diagnosed earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The worrisome situation in Zambia has triggered the development of various TB strategies and public health efforts [15, 16]. Despite a longstanding DOT and sensitisation programmes, Zambia still struggles with optimizing its NTP to avoid pre-hospital delay and treatment non-compliance of TB patients.…”
Section: Introductionmentioning
confidence: 99%